Cloud Based Application Server for Universities: A New Approach - Shuayib Bakhtiar Rana, Lieutenant Commander; Md. Shaifur Rahman Chowdhury, Major; Hossain Bhuiyan, Tanvir (Department of Computer Science and Engineering, Military Institute of Science and Technology, 2013)
In the new era of technology it is often said “Now the generation is changing in every six months or less”. From this very small sentence we can understand the rapid development and growth of technology globally. Every single person is connected with data highway in various ways. But the more users are being connected, it is obvious that the performance of computing must be degraded. The most important matter here, we are concerned about the resources used in computing. Much more use of resources, whether it is hardware or software, will increase the cost of computing. Cloud computing, in this situation, gives us relaxation as it is the key way to keep computing cost within our limit. For all types of computing environment cloud plays a great role for resource sharing. Specially if we think aboutanacademicenvironmentofaneducationalinstitute,herealotnumberofusersdothe same type of work for their study, lab work etc. But if cloud can be introduced here, lot of resource requirements can be reduced. We propose a cloud based application server which can be used by all students, faculties and staffs of a university simultaneously.
Keywords: Cloud, Application, Server, Universities, Approach